Magnetic control of self-assembly and disassembly in organic materials - You-jin Jung; Hyoseok Kim; Hae-Kap Cheong; Yong-beom Lim (Nature Communications, 2023)
Abstract Because organic molecules and materials are generally insensitive or weakly sensitive to magnetic fields, a certain means to enhance their magnetic responsiveness needs to be exploited. Here we show a strategy to amplify the magnetic responsiveness of self-assembled peptide nanostructures by synergistically combining the concepts of perfect α-helix and rod-coil supramolecular building blocks. Firstly, we develop a monomeric, nonpolar, and perfect α-helix (MNP-helix). Then, we employ the MNP-helix as the rod block of rod-coil amphiphiles (rod-coils) because rod-coils are well-suited for fabricating responsive assemblies. We show that the self-assembly processes of the designed rod-coils and disassembly of rod-coil/DNA complexes can be controlled in a magnetically responsive manner using the relatively weak magnetic field provided by the ordinary neodymium magnet [0.07 ~ 0.25 Tesla (T)]. These results demonstrate that magnetically responsive organic assemblies usable under practical conditions can be realized by using rod-coil supramolecular building blocks containing constructively organized diamagnetic moieties.